(untitled) (Acta Entomologica Serbica, 2019)
Two hymenopteran species are reported for the Serbian fauna. Diprion similis, from the family Diprionidae, served as a host for the parasitoid wasp Monodontomerus dentipes, from the family Torymidae. The specimens were collected from Mt. Zlatibor in western Serbia. The parasitoid specimens were reared from the pupal stadium of the host D. similis.